Sportive university students and life satisfaction - Turgut, Murat (Birlesik Dunya Yenilik Arastirma ve Yayincilik Merkezi, 2021)
The aim of this study was to investigate the levels of life satisfaction of individuals participating in sports or physical activity within the scope of gender, age, income status, parental education level and active sports. The sample of the study consisted of 442 people from Kastamonu Province. Parametric analysis methods were used to analyse the data. Independent t-test was used to determine the difference between two groups and one-way analysis of variance was used to determine the difference between two groups. According to the findings, there was no statistically significant difference between age and income status. In other words, life satisfaction levels of the participants were found to be high. The highest mean subscale was found to be the relationship satisfaction dimension with a mean of X̄ = 4.90 and the lower mean was the overall life satisfaction sub-dimension with a mean of X̄ = 3.50. In parallel with this situation, it was determined that life satisfaction levels of the participants varied according to different variables. Keywords: Life satisfaction, physical activity, sport, students, university.
Keywords: 4. Education; 16. Peace & justice